A comparative study of the relationship between circular economy, economic growth, and oil price across South Asian countries - Apostu, Simona Andreea; Hussain, Anwar; Kijkasiwat, Ploypailin; Vasa, Laszlo (Frontiers in Environmental Science, 2022)
The pathway to economic growth is represented by circular economy. Biomass has a significant influence in a circular economy, both in terms of material products and energy provision. Present research investigates the relationship among economic growth, oil price and circular economy through biomass energy consumption in South Asian countries by using ARDL and Granger causality. The findings show all elasticities are statistically significant on short run for Pakistan, India, Bangladesh, and Sri-Lanka. On long run, coefficients of oil price for Pakistan and Sri-Lanka are positive with significant elasticities, whereas biomass energy consumption negatively associates with oil price in India and Bangladesh. Biomass energy consumption significantly impacts the economic growth of Pakistan and Bangladesh on long run, whereas India and Bangladesh show association between biomass energy consumption and GDP. As a policy implication government can create and adjust policies in order to reduce cost toward energy system and protect the environment from pollution with the adoption of biomass energy system because fossil oil and coal energy system is unfavorable to economic growth, especially across South Asia countries.